Audio visual translation of Coca Cola video “Open Happiness” Potentially Meaning to Translation from Multinations - Mujazin Mujazin (Universitas Muhammadiyah Surakarta, 2018)
Abstract-The visual and non-visual advertisement is created to attract consumer’s interest for the product, an important aspect to deliver the message is by advertising and branding the product with local wisdom and culture. As it deilivered clearly, informative and communicative it will be a solution of global market, recently the consumers are not dirrectly attracted to advertisement because the advertisement can’t transfer the message naturally. This article is qualitative research, it describes the phenomena of Coca cola branding on TV, Net. The strategy is the key success of marketting to achieve the profit and bring the messages delivered. The global branding delivered by Coca cola opens insight of strategy to grasp the prospective consumers. The topic of the recent video advertisement on TV, Net called open happiness.This strategy is created to fasten the effect of advertisement for consumers, positive response to buy the product. However there is a challenge to opt the right culture for branding the product. It has great success because it uses both methods of marketing textual and graphic. Those two reflect on political and cultural aspects of targetted language. This is done to attract the consumers topurchase the products and gain the maximum benefits. Benefits of capital and trust. Ads on TV, Net with the topic open happiness uses both textual and graphic.Keyword : advertisement, audio visual translation, branding, deliver.